Hyperglycemia, assessed according to HbA1c, and future risk of venous thromboembolism: the Tromsø study. (March 2014) - Lerstad, G.; Brodin, E. E.; Enga, K. F.; Jorde, R.; Schirmer, H.; Njølstad, I.; Svartberg, J.; Brækkan, S. K.; Hansen, J.‐B.
Summary Background HbA1c, a marker of average plasma glucose level during the previous 8–12 weeks, is associated with the future risk of cardiovascular disease and all‐cause mortality. Objectives To examine the association between hyperglycemia, assessed according to HbA1c, and the future risk of venous thromboembolism (VTE) in a population‐based cohort. Methods HbA1c was measured in 16 156 unique subjects (25–87 years) who participated in one or more surveys of the Tromsø study (Tromsø 4, 1994–1995; Tromsø 5, 2001–2002; and Tromsø 6, 2007–2008). All subjects were followed, and incident VTE events were recorded up to 31 December 2010. Results There were 333 validated first VTE events, of which 137 were unprovoked, during a median follow‐up of 7.1 years. HbA1c was not associated with the future risk of VTE in analyses treating HbA1c as a continuous variable, or in categorized analyses. The risk of VTE increased by 5% per one standard deviation (0.7%) increase in HbA1c (multivariable‐adjusted hazard ratio [HR] 1.05; 95% confidence interval [CI] 0.97–1.14), and subjects with HbA1c ≥ 6.5% had a 27% higher risk than those with HbA1c < 5.7% (multivariable‐adjusted HR 1.27; 95% CI 0.72–2.26). There was no significant linear trend for an increased risk of VTE across categories of HbA1c (P = 0.27). Conclusions Serum levels of HbA1c were not associated with the future risk of VTE in multivariable analysis. Our findings suggest that hyperglycemia does not play an important role in the pathogenesis of VTE.